Secure Electronic Healthcare Records (SEHR) Using Blockchain Model based on Elliptic Curve Cryptography (ECC) - Ammar Shihab; Ali Kashmar (Iraqi Journal of Science, 2026)
This paper proposes a blockchain-based system for managing Electronic Health Records (EHR) to address patient demands for immediate access to health information while ensuring privacy and security. It introduces a framework that includes five key entities: Registration Centre (RC), Patients, Doctors, Mobile Devices, and Blockchain (BC), and emphasizes the use of Elliptic Curve Cryptography (ECC) for enhanced security.The system utilizes a decentralized blockchain platform to securely store patient data and carry out operations, employing smart contracts for efficient and secure transactions. Access through the MetaMask wallet allows authorized users, such as doctors and patients, to easily manage and retrieve records while maintaining privacy. The approach aims to improve efficiency, trust, and security in health data storage and transfers.Overall, the proposed solution enhances interoperability, auditability, and automation while ensuring data privacy and security, demonstrating its viability across various blockchain networks.